THE ROLE OF LEADERSHIP IN THE WORK MOTIVATION OF STATE CIVIL APPARATUSES IN PUNCAK CENDERAWASIH VILLAGE OFFICES, SORONG CITY - Salmah, Ummu; Kadir, Muhammad Arifin Abd; Ali, Muhammad; Kamaluddin, Kamaluddin (Universitas Negeri Yogyakarta, 2023)
Work motivation that encourages enthusiasm or enthusiasm for work following organizational goals. And the challenge is one employee with another employee who is driven by different work urges. Many things affect a person's work motivation both from within the individual and external factors. The role of leadership is one of the factors that influence employee work motivation in providing services. The leadership role is at the core of the organization's progress and retreat. Based on the explanation above, this study aims to determine the role of leadership in increasing the work motivation of the State Civil Apparatus in Puncak Cendrawasih Village, Sorong City. The research method used is qualitative. Then the data collection techniques include observation, interviews, and documentation. Data analysis techniques are the way the data is obtained in the study so that conclusions are obtained, and both primary data and secondary data are carried out to complement the data from the results obtained. This study shows that the role of leadership in Puncak Cendrawasih Village, Sorong City is not yet optimal in increasing employee performance motivation. This can be seen from the lack of encouragement to encourage the work system, not giving praise or praise to employees who excel, lack of work discipline, less satisfaction with the work system in the office, and lack of employees towards their employees. The decisions taken by the leadership in Puncak Cendrawasih Village, Sorong City have not been to the expectations of their employees.